2011
DOI: 10.2215/cjn.05060610
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Calcium-Containing Phosphate Binders in Incident U.S. Dialysis Patients

Abstract: SummaryBackground and objectives Few studies have assessed the association between phosphate binder use and hard outcomes in dialysis patients. Furthermore, the comparative effectiveness of calcium carbonate and acetate is untested. We studied the association between use versus nonuse of calcium-containing phosphate binders (CCPBs) and mortality from any cause. We also tested whether mortality differed among users of individual CCPBs.Design, setting, participants, & measurements A nationally representative pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 19 publications
1
27
0
1
Order By: Relevance
“…40 In a study on 3,603 incident dialysis patients, 77.5% used a calcium-based binder, while 22.5% did not. Baseline use of calcium-based binders was associated with an adjusted 19% lower mortality rate compared …”
Section: Calcium-based Phosphate Bindersmentioning
confidence: 99%
See 1 more Smart Citation
“…40 In a study on 3,603 incident dialysis patients, 77.5% used a calcium-based binder, while 22.5% did not. Baseline use of calcium-based binders was associated with an adjusted 19% lower mortality rate compared …”
Section: Calcium-based Phosphate Bindersmentioning
confidence: 99%
“…No mortality differences were observed between calcium acetate and calcium carbonate users in crude, adjusted, or propensitymatched analyses. 40 A more recent calcium-based formulation comprises calcium acetate and magnesium carbonate (CaMg). In a randomized controlled study comparing CaMg and calcium carbonate, lower P and calcium levels were observed in the group of patients treated with CaMg.…”
mentioning
confidence: 99%
“…The authors speculated that the observation might be explained by modulation of direct effect of phosphorus or compensatory mechanisms such as FGF23 on patient survival [33]. However, this reduction in mortality was not observed in incident dialysis patients treated with calciumcontaining binders, either calcium acetate or calcium carbonate [34]. Phosphorus binders lower serum phosphorus and also lower FGF23 levels.…”
Section: Phosphorus Bindersmentioning
confidence: 99%
“…It has been studied in many well-designed small pilot studies and the response to the agent correlates with a reduction in antibodies to the M-type phospholipase A2 receptor. [12][13][14][15] In this issue of JASN, Ruggenenti et al 16 describe the course of 100 patients with persistent, angiotensin converting enzyme inhibitor-treated, idiopathic membranous nephropathy given rituximab and followed over a median time of 29 months. The study includes 68 patients with new onset disease and 32 patients with prior immunosuppressive therapy.…”
Section: Disclosuresmentioning
confidence: 99%
“…They found, using different types of analyses, that treatment with phosphate binders was independently associated with decreased mortality risk compared with no treatment. However, Winkelmayer et al, 15 who compared use versus nonuse of calcium-containing phosphate binders in incident dialysis patients, did not observe any mortality differences, using multivariate and propensity score-matched Cox regression models.…”
mentioning
confidence: 95%